Women in dramatic place and time : contemporary female characters on stage - Cousin, Geraldine (London ; New York : Routledge, 1996)
In Women in Dramatic Place and Time Geraldine Cousin presents detailed analyses of a wide range of plays by British women dramatists from the last two decades. Cousin focuses on women's dramatic efforts to 'speak out' from the ideological spaces in which they have been positioned. She attends to the processes through which female characters have found their voices, and tracks their journeys into previously uninhabited territories.
The plays considered include Queen Christina (Pam Gems), My Mother Said I Never Should (Charlotte Keatley), Real Estate (Louise Page), The Grace of Mary Traverse (Timberlake Wertenbaker), Leave Taking (Winsome Pinnock), The Skriker (Caryl Churchill), and After Easter (Anne Devlin).
Women in Dramatic Place and Time offers exciting insights into the diversity and excellence of contemporary plays by women. It is invaluable reading for students of contemporary British theatre, literature, and women's studies, as well as anyone interested in women's writing.
Prologue: The room and the wilderness: Rutherford and Son and Granite -- 1. Wildernesses Reclaimed -- 2. Related Spaces, Related Lives -- 3. Time-Travellers and Disorderly Women -- 4. Retellings -- 5. Quests for Maps -- 6. Correspondent Worlds: Encounters with fairies and angels.
Includes bibliographical references (p. 206-208) and index.
Keywords: English drama -- 20th century -- History and criticism; Women in literature